IgA dominates the early neutralizing antibody response to SARS-CoV-2 - Delphine Sterlin; Alexis Mathian; Makoto Miyara; Audrey Mohr; François Anna; Laetitia Claër; Paul Quentric; Jehane Fadlallah; P. Ghillani; Cary Gunn; Rick Hockett; Sasi Mudumba; et al. (2020)
Abstract A major dogma in immunology has it that the IgM antibody response precedes secondary memory responses built on the production of IgG, IgA and, occasionaly, IgE. Here, we measured acute humoral responses to SARS-CoV-2, including the frequency of antibody-secreting cells and the presence of specific, neutralizing, antibodies in serum and broncho-alveolar fluid of 145 patients with COVID-19. Surprisingly, early SARS-CoV-2-specific humoral responses were found to be typically dominated by antibodies of the IgA isotype. Peripheral expansion of IgA-plasmablasts with mucosal-homing potential was detected shortly after the onset of symptoms and peaked during the third week of the disease. While the specific antibody response included IgG, IgM and IgA, the latter contributed to a much larger extent to virus neutralization, as compared to IgG. However, specific IgA serum levels notably decrease after one month of evolution. These results represent a challenging observation given the present uncertainty as to which kind of humoral response would optimally protect against re-infection, and whether vaccine regimens should consider boosting a potent, although, at least in blood, fading IgA response. One sentence Summary While early specific antibody response included IgG, IgM and IgA, the latter contributed to a much larger extent to virus neutralization.